Metaphysical Horizon in Wanda Dynowska’s Indian Poems (Indian Journal of Social Science and Literature (IJSSL), 2024)
The article concerns the works of literature published by the Polish poet Wanda Dynowska (1888-1971). The sacred theme, which is ubiquitous in her works, will be analysed and interpreted. As a writer, translator, social activist and promoter of Indian culture in Poland and Polish culture in India and Tibet, Dynowska was an extraordinary woman. She does not belong to the group of the most outstanding Polish poets such as Wisława Szymborska, Czesław Miłosz or Zbigniew Herbert, yet her poetry is definitely unique due to the subject matter that is hardly found in Polish literature and the empirical sources of her work. What is more, Dynowska came to India in 1935. The experience of living in Hindu culture had a tremendous impact on her poems. Therefore, her poems and essays were published thanks to Dynowska’s infatuation with Hindu culture, the writings of Krishnamurti and the spiritualism of Hinduism and Buddhism. The following works Mahayana Buddhism, On the subject of nature and art, Hindu poems were published thanks to the enterprise, which was funded by Wanda Dynowska and Maurycy Frydman. Indeed, they owed it to a Polish-Indian Library that was located in Madras. Surprisingly, only a few scholars such as Kazimierz Tokarski, Izabela Trzcińska and Ewa Dębicka-Borek scrutinised Dynowska’s poetry at that time. In this article the poems titled Where are you?, My path, Shiva's Night, Near and far are interpreted. Furthermore, the philosophy proclaimed by Mircea Eliade, Gerardus van der Leeuw and Rudolf Otto is intertwined with a novel analysis of the poems. In addition, Polish sacrologists such as Stefan Sawicki and Zofia Zarębianka had a major impact on interpreting Dynowska’s poetry. Consequently, the interpretation of the works shows that the sacred in the works of Wanda Dynowska is based on respect for the followers of each religion combining Christian, Buddhist and Hindu influences.